2022
DOI: 10.1177/07342829221106585
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Invariance and Relationships Among School Connectedness, Cyberbullying, and Cybervictimization: A Comparison Among Canadian, Chinese, and Tanzanian Adolescents

Abstract: The aim of the present study was to evaluate the measurement invariance of the School Connectedness Scale for Chinese, Canadian, and Tanzanian adolescents, and to explore the inter association between school connectedness and cyberbullying/cybervictimization. Participants included 3872 adolescents from urban settings in China ( N= 2053, M age=16.36 years, SD = 1.14 years; 44.6% boys), Canada ( N = 642, M age = 12.13 years, SD = 0.77 years; 50.1% boys), and Tanzania ( N = 1056 , M age=15.87 years, SD = 2.03 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Therefore, all these differences could lead to culture-related construct-irrelevant variance. Since these findings were not reported by previous researchers (Furlong et al, 2011; He et al, 2019; Law et al, 2022; Waters et al, 2010), further research is needed to validate these findings.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Therefore, all these differences could lead to culture-related construct-irrelevant variance. Since these findings were not reported by previous researchers (Furlong et al, 2011; He et al, 2019; Law et al, 2022; Waters et al, 2010), further research is needed to validate these findings.…”
Section: Discussionmentioning
confidence: 58%
“…The results suggested that five SSBS items for grades 4 and 8 demonstrated differences at various theta points among these countries. These identified differences indicated a violation of the measurement invariance of the SSBS across different cultural contexts (AERA et al, 2014;Law et al, 2022;Waters et al, 2010). Scale measurement invariance is essential for international assessment programs as it ensures that the measurement of a construct in one cultural or linguistic group is comparable to the measurement of the same construct by the same scale in a different cultural or linguistic group (AERA et al, 2014;Davidov et al, 2014;Jia et al, 2018).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 3 more Smart Citations